Foreign words, Gramophones and Truth in “Politics and the English Language” by George Orwell (1946) - Pierre Guerlain (Revue LISA)
This paper analyses Orwell’s stance as far as the use of foreign words in English is concerned and relates it to his larger political and philosophical views. It deconstructs the perception of Orwell as a linguistic chauvinist and focuses on the affinities between Orwell, Russell and Chomsky to make a point about the fight between post-modernists and so-called rationalists.